The Measurement of SMEs Perception and Awareness in Banten Province, Indonesia - Sanusi, Fauji; David Ramdansyah, Agus (British Journal of Marketing Studies, 2023)
The research aims to study about the awareness and perceptions of the SMEs palm sugar in Lebak district, Banten Province-Indonesia on Fintech model such as Peer-to-Peer lending and crowd funding in developing their business. The researchers designed as many as 17 questions to conduct a survey related to the research variable. Descriptive analysis is applied by using Microsoft Office Excel data processing. Frequency distribution and central size are used for data analysis. The results show that awareness level of the most respondents is still insufficient on Peer-to-Peer lending and crowd funding as alternative financing instruments. The majority of them have a positive perception of FinTech development. It can be concluded that the level of awareness of most respondents is still very limited, especially on P2P loans, Crowdfunding and other FinTech services provided by non-bank financial institutions. They need to increase awareness level of palm sugar SMEs by related parties such as the government.